How do general practitioners access guidelines and utilise electronic medical records to make clinical decisions on antibiotic use? Results from an Australian qualitative study. Issue 8 (5th August 2019) - Biezen, Ruby; Roberts, Cassandra; Buising, Kirsty; Thursky, Karin; Boyle, Douglas; Lau, Phyllis; Clark, Malcolm; Manski-Nankervis, Jo-Anne
Abstract : Objective: This study aimed to explore how general practitioners (GPs) access and use both guidelines and electronic medical records (EMRs) to assist in clinical decision-making when prescribing antibiotics in Australia. Design: This is an exploratory qualitative study with thematic analysis interpreted using the Theory of Planned Behaviour (TPB) framework. Setting: This study was conducted in general practice in Victoria, Australia. Participants: Twenty-six GPs from five general practices were recruited to participate in five focus groups between February and April 2018. Results: GPs expressed that current EMR systems do not provide clinical decision support to assist with antibiotic prescribing. Access and use of guidelines were variable. GPs who had more clinical experience were less likely to access guidelines than younger and less experienced GPs. Guideline use and guideline-concordant prescribing was facilitated if there was a practice culture encouraging evidence-based practice. However, a lack of access to guidelines and perceived patients' expectation and demand for antibiotics were barriers to guideline-concordant prescribing. Furthermore, guidelines that were easy to access and navigate, free, embedded within EMRs and fit into the clinical workflow were seen as likely to enhance guideline use. Conclusions: Current barriers to the use of antibiotic guidelines include GPs' experience, patient factors, practice culture, and ease of access and cost of guidelines. To reduce inappropriate antibiotic prescribing and to promote more rational use of antibiotic in the community, guidelines should be made available, accessible and easy to use, with minimal cost to practicing GPs. Integration of evidence-based antibiotic guidelines within the EMR in the form of a clinical decision support tool could optimise guideline use and increase guideline-concordant prescribing.